ECLECTIC METHOD: AN ALTERNATIVE TO SUPPORT GRAMMAR MASTERY TO TWELVE GRADERS - Kiswati Kiswati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
This research is aimed to know the use of Eclectic Method towards students grammar mastery. Due to the low grammar score and less motivation of the students to learn grammar as one of the material that should be mastered by the students integratedly with the other material. The research was a two-cycle classroom action research conducted to twelfth graders of social department at MAN 5 Jombang. This study used grammar tests, observation sheet and field notes as the instruments. The research finding proved that eclectic method was effective to be conducted in teaching English, mainly in grammar class. The data showed that the grammar score was improved significantly from the average score of 55.87 in preliminary study to become 76.65 in cycle 1 and 88.19 in cycle 2. The participation of the students during the cycle was also improved from cycle to cycle.